Living with ambiguity : religious naturalism and the menace of evil - Crosby, Donald A. (State University of New York Press, 2008)
Religion of nature, as it is laid out and explained here, confronts this problem and offers a comprehensive, sustaining, and fully adequate way of conceiving and living a religious life."--BOOK JACKET.